Clinical relevance of inflammatory markers in the evaluation of severity of ulcerative colitis: A retrospective study - He, Tao; Song, Lian-Qiang; Weng, Xiao-Yu; Pan, Peng; Ding, Hui; Liu, Mei-Qin; Qiu, Shi-Lin; Sun, Shan-Ming (Open life sciences, 2025)
This study aimed to investigate the clinical relevance of inflammatory markers in the severity assessment of ulcerative colitis (UC). The inflammatory markers included the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and calcium ion (Ca ) levels. A retrospective analysis was on 110 patients with UC and 52 patients with irritable bowel syndrome (IBS), admitted to Weifang People’s Hospital between June 2019 and February 2021. UC severity was classified using the modified Mayo score and the Montreal classification system. The study assessed the predictive accuracy and correlation of these inflammatory markers with UC severity and extent. Levels of NLR, PLR, CRP, ESR, and Ca were significantly elevated in individuals with UC compared to those with IBS. Among patients with UC, significant differences in these markers were observed across varying severity levels as defined by the modified Mayo score. However, aside from ESR, no significant differences were noted in NLR, PLR, CRP, or Ca levels across groups defined by lesion extent. Receiver operating characteristic curve analysis indicated that NLR exhibited the highest predictive accuracy for UC, with a cut-off value of 2.603 yielding a sensitivity of 0.545, specificity of 0.288, and an area under the curve (AUC) of 0.896. The combined use of NLR, PLR, CRP, ESR, and Ca demonstrated superior predictive performance, achieving an AUC of 0.972, sensitivity of 0.927, and specificity of 0.923 at a cut-off value of 0.455. NLR, PLR, CRP, ESR, and Ca exhibit predictive value for UC, with NLR demonstrating the highest individual predictive performance. The combined use of these markers enhances predictive accuracy, highlighting their potential application in clinical practice for the evaluation of severity UC. Due to ethical considerations at our institution, the IBS group was used as a substitute for healthy controls. The IBS group was included solely for the calibration and testing of inflammatory biomarkers, as well as for subsequent analysis of their role in assessing UC severity.